Tumor-Derived Apoptotic Vesicles: With Death They Do Part - Muhsin-Sharafaldine, Morad-Remy; McLellan, Alexander D. (Frontiers in Immunology, 2018)
Tumor cells release lipid particles known as extracellular vesicles that contribute to cancer metastasis, to the immune response, and to thrombosis. When tumors are exposed to radiation or chemotherapy, apoptotic vesicles are released in abundance when the plasma membrane delaminates from the cytoskeleton from the cell membrane. Recent studies have suggested that apoptotic vesicles are distinct from the extracellular vesicles released from living cells such as exosomes or microvesicles. Depending on their treatment conditions, tumor-released apoptotic vesicles have been suggested to either enhance or suppress anti-cancer immunity. In addition, tumor-derived apoptotic vesicles have been identified to possess high levels of procoagulant activity that can potentially increase the thrombotic state in cancer patients undergoing chemotherapy or radiotherapy. Since apoptotic vesicles are one of the least appreciated type of extracellular vesicles, we focus in this review on the distinctive characterization of tumor apoptotic vesicles and their proposed mechanistic effects on cancer immunity, coagulation, and metastasis.